Metabolite Profiling of Malaysian Gracilaria edulis Reveals Eplerenone as Novel Antibacterial Compound for Drug Repurposing Against MDR Bacteria - Asghar, Ali; Tan, Yong-Chiang; Shahid, Muhammad; Yow, Yoon-Yen; Lahiri, Chandrajit (Frontiers in Microbiology, 2021)
With a continuous threat of antimicrobial resistance on human health worldwide, efforts for new alternatives are ongoing for the management of bacterial infectious diseases. Natural products of land and sea, being conceived to be having less side-effects, pose themselves as welcome relief. In this respect, we have taken a scaffolded approach to unearth the almost unexplored chemical constiutents of Malaysian red seaweed, Gracilaria edulis. Essentially, a preliminary evaluation of the ethyl acetate and acetone solvent extracts, among a series of six such, revealed potential antibacterial activity against six MDR species namely, Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella enterica, methicillin-resistant Staphylococcus aureus (MRSA), Streptococcus pyogenes and Bacillus subtilis. A detailed analyses of the inlying chemical constitutents, through LC-MS and GC-MS chromatographic separation, revealed a library of metabolic compounds. These were led for further virtual screening against selected key role playing proteins in the virulence of the aforesaid bacteria. To this end, a detailed predictive pharmacological analyses added up to reinforce Eplerenone as a natural alternative from the plethora of the plausible bioactives. Our work adds onto the ongoing effort to re-discover and repurpose biochemical compounds with an aim to combat the antimicrobial resistance offered by the Gram-positive and the -negative bacterial species.